Day 2 Wed, March 22, 2017 2017
DOI: 10.2118/184749-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing CT Material Properties for Extended Reach Operations

Abstract: There is a demand in the industry for coiled tubing (CT) that can safely reach significantly farther in horizontal wells than the current, steel based technology can reach. Some have suggested that CT composed of lighter materials could maintain a neutral or positive buoyancy (floating) in the horizontal section and thus be capable of reaching extraordinary total depths without exceeding their yield limit. However, several other aspects of CT operations must be considered for a complete assessment of extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…According to the results of studies of total corrosion in five working solutions, it was found that the corrosion rate in acidic [22,23] solutions (I, II) is significantly higher than in neutral [24] (III, IV, and V). For ease of analysis, the results of corrosion studies are presented separately for acidic and neutral working solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of studies of total corrosion in five working solutions, it was found that the corrosion rate in acidic [22,23] solutions (I, II) is significantly higher than in neutral [24] (III, IV, and V). For ease of analysis, the results of corrosion studies are presented separately for acidic and neutral working solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Continuing to work in this direction, the authors want to consider in more detail the action of gas hydrates on the corrosion resistance [18,19,24] of CT pipes. Especially, action acidic gases such as H 2 S and CO 2 , which are components of gas hydrates, and dissolve in water, can accelerate the internal pitting corrosion of CT pipes.…”
Section: Discussionmentioning
confidence: 99%